Ecological Predictors of Parental Beliefs about Infant Crying in a Randomized Clinical Trial of ABC. Issue 5 (3rd September 2022) - Thorpe, Daneele; Silver, Jamilah; Perrone, Laura; DeSantis, Nicole; Dash, Allison; Rodriguez, Melanie; Beras-Monticciolo, Erasma; Bernard, Kristin
ABSTRACT: Objective: Attachment theory suggests that parent responsiveness to infant distress predicts secure parent–child attachment and subsequent healthy child development. While much is known about microsystem factors that interfere with responsive caregiving, there is a paucity of research investigating how exosystem factors, such as neighborhood crime, affect parenting. Method: In a sample of 200 diverse caregivers and their 5- to 21-month-old infants ( M = 11.82; 49% male), we leveraged data from a randomized clinical trial of Attachment and Biobehavioral Catch-up (ABC), an attachment-based intervention, to assess whether individual level burden (indicated by single-parent status, low income, residential instability, young parenthood, parental psychopathology, and own history of early adversity) and neighborhood crime density (geocoded within a 500 ft radius of parent's residence) were associated with their beliefs about infant crying, an indicator of responsive parenting. Results: Consistent with Bronfenbrenner's ecological systems' theory of development, both greater exposure to individual burden indicators and greater neighborhood crime density predicted greater maladaptive beliefs about infant crying, suggesting that contextual factors outside the household are associated with parenting cognitions. Further, when accounting for the effect of crime and individual burden on parental beliefs about infant crying, participation in the ABC intervention was effective in reducing maladaptive parenting beliefs. Conclusions: We consider implications for multi-level intervention approaches that target family processes, neighborhood-level factors, and policy initiatives to promote community wellbeing and positive child development.